Decreased Plasma Levels of Growth Differentiation Factor 11 in Patients With Schizophrenia: Correlation With Psychopathology and Cognition - Yang, Zhao-xi; Zhan, Jin-qiong; Xiong, Jian-wen; Wei, Bo; Fu, Yong-hui; Liu, Zhi-peng; Tu, Ya-ting; Yang, Yuan-jian; Wan, Ai-lan (Frontiers in Psychiatry, 2020)
Schizophrenia is linked with abnormal neurodevelopment, on which growth differentiation factor 11 (GDF-11) has a great impact. However, a direct evidence linking GDF-11 to the pathophysiology of schizophrenia is still lacking. The current study aimed to investigate the relationship between plasma GDF-11 levels and both psychopathological symptoms and cognitive function in schizophrenia. Eighty-seven schizophrenia patients and 76 healthy controls were enrolled in the present study. The symptomatology of schizophrenia was evaluated using the Positive and Negative Syndrome Scale (PANSS). Cognitive function was assessed by Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) including twelve neurocognitive tests in five aspects of cognitive function. Plasma GDF-11 levels were determined by enzyme-linked immunosorbent assay (ELISA). We found that plasma levels of GDF-11 were significantly lower in schizophrenia patients relative to healthy controls. Correlation analysis showed significant negative correlations between the GDF-11 levels and the PANSS total score, the positive symptoms score, the negative symptoms score or the general score. Additionally, positive associations were observed between plasma GDF-11 levels and the visuospatial/constructional, attention, immediate memory, or delayed memory in patients. Partial correlation analysis showed that these correlations were still significant after adjusting for age, gender, education years, body mass index, duration of illness, and age of onset except for the visuospatial/constructional and attention index. Multiple regression analysis revealed that GDF-11 was an independent contributor to the immediate memory, delayed memory and RBANS total score in patients. Collectively, the correlations between plasma GDF-11 and psychopathological and cognitive symptoms suggest that abnormal GDF-11 signaling might contribute to schizophrenic psychopathology and cognitive impairments and GDF-11 could be a potential and promising biomarker for schizophrenia.